Globalisasi dan krisis ekologi: upaya konservasi dalam perspektif fikih lingkungan - Mudhofir Abdullah (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
Environmental crisis has been recognized as a global phenomenon and has come at a level that veryendangers human life on earth. Environmental crisis is not a matter of a nation, race, religion, or group.It has been a common problem and requires global cooperation to overcome barriers regardless ofreligion and race. Within this framework, every religion and traditions required to contribute in jointactions to overcome the environmental crisis. This is so, because the efforts of political and secular laware considered no longer sufficient to resolve the tragedies of today’s ecological problem on earth.Therefore, this paper will explore the perspective of Environmental Fikih in the context of a globalmovement in overcome the environmental crisis.